The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1128/spectrum.02188-22
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Vibrio parahaemolyticus Underlying the Wrinkly and Smooth Phenotypes

Abstract: We showed that Vibrio parahaemolyticus was able to naturally and reversibly switch between wrinkly and smooth phenotypes and disclosed the gene expression profiles related to wrinkly-smooth switching, showing that the significantly differentially expressed genes between the two colony morphology phenotypes were involved in various biological behaviors, including virulence factor production, biofilm formation, metabolism, adaptation, and colonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 83 publications
0
15
0
Order By: Relevance
“…The data presented here showed that Mg 2+ not only affected the swimming and swarming motility but also the gene expression of both two flagellar systems. Flagellar gene expression in V. parahaemolyticus is strictly regulated by various factors, including regulators such as ToxR [ 54 ], LafK [ 55 ], H-NS [ 56 ] and CalR [ 57 ], chemicals such as chloramphenicol [ 44 ] and l -arabinose [ 44 ], and different biological behavior processes such as biofilm formation [ 36 ] and EPS phase variation [ 44 ]. The resented data further enriched the regulatory networks of flagellar genes in V. parahaemolyticus .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The data presented here showed that Mg 2+ not only affected the swimming and swarming motility but also the gene expression of both two flagellar systems. Flagellar gene expression in V. parahaemolyticus is strictly regulated by various factors, including regulators such as ToxR [ 54 ], LafK [ 55 ], H-NS [ 56 ] and CalR [ 57 ], chemicals such as chloramphenicol [ 44 ] and l -arabinose [ 44 ], and different biological behavior processes such as biofilm formation [ 36 ] and EPS phase variation [ 44 ]. The resented data further enriched the regulatory networks of flagellar genes in V. parahaemolyticus .…”
Section: Resultsmentioning
confidence: 99%
“…In this work, the data showed that all the cps genes ( cpsA-K ) and four scv genes were significantly downregulated by Mg 2+ ( Table 1 ). Although both the cps and scv gene loci are involved in the synthesis of EPS and biofilm formation, but only the cps gene cluster affects the switching between wrinkled and smooth colony phenotype of V. parahaemolyticus [ 16 , 36 ], indicating that the cps gene cluster may contribute more to EPS synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intracellular c‐di‐GMP concentration was measured as reported previously (Liu et al, 2022; Wu, Li, et al, 2022), with some modifications. Briefly, the overnight V. parahaemolyticus cultures were subcultured into a fresh MLB medium or on a swarming plate at 37°C for 8 h. When required, the strains in the MLB medium were incubated for 3 (low cell density, OD 600 ≈ 0.1) or 9 h (high cell density, OD 600 ≈ 1.0).…”
Section: Methodsmentioning
confidence: 99%